Language Comprehension in Young People with Severe Cerebral Palsy in Relation to Language Tracts: A Diffusion Tensor Imaging Study - Harlaar, Laurike; Pouwels, Petra J.; Geytenbeek, Joke; Oostrom, Kim; Barkhof, Frederik; Vermeulen, R. Jeroen (Neuropediatrics, 2013)
Patients with severe cerebral palsy (CP) often have poor speech ability but potentially better language comprehension. The arcuate fasciculus and the extreme capsule are two important language tracts between the Wernicke and Broca areas. Using diffusion tensor imaging, we visualized language tracts and pyramidal tracts in both hemispheres in 10 controls (5 to 18 years) and 5 patients (5 to 23 years) with severe CP. Language comprehension was assessed with a recently designed instrument (the Computer-Based instrument for Low motor Language Testing [C-BiLLT]). The language tracts were visualized in all control children and in four CP patients. In one CP patient without any objective language comprehension skills, no language tract could be visualized. Both language and pyramidal tracts were smaller in patients than in controls. These preliminary data indicate a relation between language tracts and language skills. Further research is necessary to study the value of structural integrity of language tracts in predicting language comprehension in CP patients.
Keywords: cerebral palsy; language tracts; magnetic resonance imaging; diffusion tensor imaging